Detours on the Path to a European Big Data Economy - Barbara Engels (Intereconomics, 2017)
As envisioned by the European Commission, national boundaries are supposed to disappear under the Digital Single Market. Many small and medium-sized companies (SMEs) are not aware of the significant potentials and promises of big data for their business activities and models.
Keywords: 330